Synthesis and Crystal Structure of a Novel Homo[2]Heterocalix[2]arene[2]triazines containing Acridine Moiety - Wang, Rui-Xiao; Mu, Lan; Zeng, Xi; Sun, Qiang; Chen, Yi; Li, Jun (Asian Journal of Chemistry, 2013)
A novel homo[2]heterocalix[2]arene[2]triazine containing acridine moiety was synthesized and its structure was characterized by NMR, IR and MS spectroscopy, its structure was confirmed by single crystal X-ray analysis. It's crystallization in the monoclinic system (space group, P21/n). It is clearly suggested that this compound was 1,3-alternate conformation with C2v symmetry. The multiple intermolecular hydrogen bond interactions led to the formation of an infinite one-dimensional chain structure and a two-dimensional zigzag layered structure.